Awareness about oral pathology specialty among medical professionals in hospitals under Kerala Health Services Department in Malappuram district in Kerala, India - Thorakkal Shamim
Background and Aim: There is a paucity of information about awareness about oral pathology speciality among medical professionals. To the best of my knowledge, this is the first study to be reported in literature. This study aimed to assess and create awareness of oral pathology specialty among medical professionals in hospitals under Kerala Health Services Department in Malappuram district in Kerala. Materials and Methods: The study was conducted between January 2018 and April 2018. The printed and validated questionnaire regarding oral pathology specialty was supplied to medical professionals in hospitals under Kerala Health Service Department in Malappuram district. The questionnaire comprised of the demographic data of the participants, including age, gender, position, and years of experience, and basic facts about oral pathology speciality. Results: Most participants surveyed (91.7%) were aware of the oral pathology specialty. In total, 77.8% of medical professionals refer oral pathology cases to general pathologists for histopathology report. However, 41.7% of medical professionals know about the new terminology potentially malignant oral disorders and their histopathological interpretation. Approximately, 33.33% of medical doctors were aware about common oral cancer (squamous cell carcinoma) grading. Conclusion: Medical professionals are aware of oral pathology specialty. The stance of referring and consulting oral pathologists for oral pathology cases for histopathology report is poor.